Hemorrhagic risk factors of endovascular onyx embolization of intracranial dural arteriovenous fistulas - Liu, Peng (Interv Neuroradiol, 2020)
BACKGROUND AND PURPOSE: Hemorrhagic complication is a disastrous complication of intracranial dural arteriovenous fistulas (DAVFs) embolization. This study was to analyze the possible risk factors for the hemorrhagic complication caused by endovascular embolization of DAVFs. METHODS: From January 2012 to July 2016, a total of 267 patients with intracranial DAVFs received endovascular Onyx embolization at our hospital. The demographic information, clinical presentation, angiographic features, endovascular treatment and hemorrhagic complications were reviewed. Univariate and multivariate logistic regression analyses were performed to evaluate the risk factors contributing to the post-procedural hemorrhagic complications. RESULTS: In 267 patients of DAVF treated with endovascular embolization, procedure-related hemorrhagic complication occurred in 12 (4.5%) patients. Univariate and multivariate logistic regression analyses showed that the pial arterial supplier (OR 13.630; 95% CI, 1.556–119.368; P = 0.018), giant venous aneurysm (OR 15.196; 95% CI, 2.505–92.183; P = 0.003) and Onyx volume ≥ 6 ml (OR 1.138; 95% CI, 1.006–1.288; P = 0.040) were significant factors associated with these hemorrhagic complications. CONCLUSIONS: Hemorrhagic complications associated with endovascular DAVF embolization are not negligible. The pial arterial supplier, giant venous aneurysm and higher Onyx volume in one session may be risk factors for endovascular DAVF embolization.